THE USE OF THE ECLECTIC METHOD IN AN ENGLISH LANGUAGE CLASSROOM FOR LEARNING SPECIFIC SKILLS - Julia R. Sevy Biloon (Universitas Sembilanbelas November Kolaka, 2016)
The purpose of this article is to demonstrate the need of basing activities, tasks and skill learning in the English language classroom on not just one approach, model or method in order to create a whole diverse learning environment. This method of teaching and creating engaging English language activities is based on the eclectic approach discussed by Kumar (2013) who states how this method allows the students to have less stress while learning, recognize very clear learning points, and complete multiple tasks while participating in a high interactive class with energetic learning experiences and quick necessary results. It will specifically look at how the use of various approaches, theories and models used in the English language classroom in Ecuador can create an environment that intrinsically allows the learner to be more comfortable, learn faster, and gain more out of a class in a shorter amount of time. This is fundamental because the authors personal experience in high school and university level shows classes tend to have many students (30 or more) and curriculum is created with the intent for students to learn large amounts of information, but is normally not allotted enough vital classroom face to face hours. Using the eclectic approach allows the teacher to better cover the necessary skills, tasks and activities for students to be able to learn, understand and ultimately gain the knowledge quintessential to becoming competent in speaking, reading, writing and listening in English in a large classroom setting in a shorter amount of time.